The Evaluation Of Craft Arts Productive Teacher Training Management at The Quality Assurance Development Center Vocational Education - Suranto, Eko; Susatya, Edhy; Kuat, Tri (JURNAL INOVASI DAN MANAJEMEN PENDIDIKAN, 2024)
Government training institutions are very limited and management has not been accredited. The purpose of the study was to evaluate the quality of productive teacher training management at the Quality Assurance Development Center Vocational Education in Arts and Culture, Yogyakarta. Management analysis focused on the quality of programs, services, and instructors. The research method used qualitative methods. The subjects of the study were instructors and training participants. The object of the study was the management of the implementation of productive teacher training for arts and crafts. Data collection techniques through observation, interviews, and documents. Data validation using triangulation of sources and methods. Data analysis using descriptive techniques and mathematical analysis. Research results; (1) the quality of the training program is categorized as very satisfactory (average 93.31) with details; 10% of the assessment frequency is categorized as satisfactory and 90% of the assessment frequency is categorized as very satisfactory, (2) the quality of training services is categorized as very satisfactory (average 92.42) with details; 22.5% of service elements are categorized as satisfactory and 77.5% of service elements are categorized as very satisfactory, and (3) the quality of the instructors is categorized as very satisfactory (average 93.10), with the note; the lowest average value of instructors is in the wood craft expertise concentration (90.18) and the highest average value of instructors is in the ceramic craft expertise concentration (96.21). Judging from the quality of instructors; 12% are categorized as satisfactory and 88% are categorized as very satisfactory.